Resource management in D2D communication: An optimization perspective. (1st September 2017) - Ahmad, M.; Azam, M.; Naeem, M.; Iqbal, M.; Anpalagan, A.; Haneef, M.
Abstract: Device-to-device (D2D) Communication was primarily introduced to achieve the fundamental goal of high data rates, ubiquitous coverage with low latency, energy efficiency and minimization of cost for per-information transmission. However, with the advent of new applications culminating from the plethora of different market segments, D2D communication is being foreseen as an integral part of the emerging fifth generation (5G) networks. Widespread use of D2D communication can result in numerous challenges namely, security, interference, access control, network mode selection and power allocation. In this paper, firstly, we provide an overview of D2D communication in cellular networks and secondly, an extensive review is presented relating to optimization approaches used for resource allocation in D2D paradigm. We classify the relevant work with respect to different optimization objectives being considered while formulating optimization problems. Some commonly used optimization formulations have been explained which makes this paper a foundation stone for further research in the area. A classification of optimization problem types and the relevant solution algorithms are also presented. We also discuss some candidate technologies for future D2D communication paradigm. Comprehensive coverage of the subject in this paper serves as a first step towards further research relating to the area of resource allocation in D2D paradigm.